2021
DOI: 10.1002/admi.202101428
|View full text |Cite
|
Sign up to set email alerts
|

A Dry‐Processed Al2O3/LiAlO2 Coating for Stabilizing the Cathode/Electrolyte Interface in High‐Ni NCM‐Based All‐Solid‐State Batteries

Abstract: Due to their high theoretical energy densities and superior safety, thiophosphate‐based all‐solid‐state batteries (ASSBs) are considered as promising power source for electric vehicles. However, for large‐scale industrial applications, interfacial degradation between high‐voltage cathode active materials (CAMs) and solid‐state electrolytes (SSEs) needs to be overcome with a simple, cost‐effective solution. Surface coatings, which prevent the direct physical contact between CAM and SSE and in turn stabilize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
(101 reference statements)
1
23
0
Order By: Relevance
“…On the other hand, ASSBs employing NCM@LPSCl operating at stack pressure of 3 MPa shows a comparable initial specific capacity to that of the cell operating at stack pressure of 20 MPa due to the enhanced microstructure of NCM@LPSCl. For comparison, the electrochemical performances of the electrode employing the NCM cathode materials for application in ASSBs are summarized in Table S3 (Supporting Information) 5, [32][33][34][35][36][37][38] . It is hard to compare fairly the electrochemical properties due to the different operation conditions, such as operating temperature, applied stack pressure, anode material, and electrode compositions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ASSBs employing NCM@LPSCl operating at stack pressure of 3 MPa shows a comparable initial specific capacity to that of the cell operating at stack pressure of 20 MPa due to the enhanced microstructure of NCM@LPSCl. For comparison, the electrochemical performances of the electrode employing the NCM cathode materials for application in ASSBs are summarized in Table S3 (Supporting Information) 5, [32][33][34][35][36][37][38] . It is hard to compare fairly the electrochemical properties due to the different operation conditions, such as operating temperature, applied stack pressure, anode material, and electrode compositions.…”
Section: Resultsmentioning
confidence: 99%
“…[ 167 ] It was demonstrated [ 179 ] that Li 3 B 11 O 18 interlayer (less than 10 nm thick) efficiently protected the <LiNi 0.5 Co 0.2 Mn 0.3 O 2 /L 3 PS 4 > interface from degradation on cycling and markedly improved cycle performance of the <LiNi 0.5 Co 0.2 Mn 0.3 O 2 |L 3 PS 4 |graphite> cell. The cycle performance of the <NCM|Li 6 PS 5 Cl|In‐Li> cell was increased by coating the LiNi 0.70 Co 0.15 Mn 0.15 (NCM701515) CAM with Li 4 Ti 5 O 12 interlayer [ 180 ] ; the cycle performance of the <Li(Ni 0.70 Co 0.15 Mn 0.15 )O 2 |Li 6 PS 5 Cl|In–Li> cell was improved by coating the CAM with Al 2 O 3 –LiAlO 2 shell, [ 181 ] and the cycle performance of the <Li[(Ni 0.9 Co 0.05 Mn 0.05)0.8 Co 0.2 ]O 2 |Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 |Li–In> cell was improved by coating the CAM with Al 2 O 3 –LiAlO 2 shell (≈3 nm thick). [ 182 ] It was demonstrated that <In|Li 7 P 2 S 8 I|LiNi 0.6 Co 0.2 Mn 0.2 O 2 > cell cycle life may be improved by the CAM coating with NiCo 2 S 4 nano particles; while this coating has a high electronic conductivity, [ 183 ] it efficiently prevents mutual diffusion of CAM and SSE ions.…”
Section: Stability and Conductivity Of Interfaces Between Sses And El...mentioning
confidence: 99%
“…The thio-LISICON b-Li 3 PS 4 has been used as a SSE in Ni-rich ASSLBs. [115][116][117][118][119][120] Undoubtedly, electrochemical parasitic reactions occur at electrode/electrolyte interfaces without protection. For example, ASSLBs composed of NCM622/b-Li 3 PS 4 and side reactions that occurred at the interface upon cycling were studied.…”
Section: Interface Instabilitymentioning
confidence: 99%
“…A series of coating materials have been constructed for Ni-rich cathodes, including Li + -conducting coating layers ( e.g. LiNbO 3 , 114,155–158 Li 2 ZrO 3 , 119,159,160 Li 4 Ti 5 O 12 , 161–163 LiAlO 2 , 118,164 Li 2 MoO 4 , 165 Li 3 PO 4 , 166 LiTaO 3 , 129 Li 3 B 11 O 18 , 109 LiPON, 167 LiNb 0.5 Ta 0.5 O 3 , 131,168,169 Li 0.35 La 0.55 TiO 3 , 125 Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 , 170 Li 0.35 La 0.5 Sr 0.05 TiO 3 , 171 Li 2 CO 3 –LiNbO 3 , 115 Li 2 CO 3 –Li 2 ZrO 3 172 and LiInO 2 –LiI 173 ), binary oxides ( e.g. Al 2 O 3 , 164 ZrO 2 , 174 HfO 2 175 and TiO 2 176 ) and carbon-based materials.…”
Section: Corresponding Solutions To Critical Issuesmentioning
confidence: 99%